Electronic Activation of a DNA Nanodevice Using a Multilayer Nanofilm. Issue 40 (31st August 2016) - Jeong, Hyejoong; Ranallo, Simona; Rossetti, Marianna; Heo, Jiwoong; Shin, Jooseok; Park, Kwangyong; Ricci, Francesco; Hong, Jinkee
Abstract : A method to control activation of a DNA nanodevice by supplying a complementary DNA (cDNA) strand from an electro‐responsive nanoplatform is reported. To develop functional nanoplatform, hexalayer nanofilm is precisely designed by layer‐by‐layer assembly technique based on electrostatic interaction with four kinds of materials: Hydrolyzed poly(β‐amino ester) can help cDNA release from the film. A cDNA is used as a key building block to activate DNA nanodevice. Reduced graphene oxides (rGOs) and the conductive polymer provide conductivity. In particular, rGOs efficiently incorporate a cDNA in the film via several interactions and act as a barrier. Depending on the types of applied electronic stimuli (reductive and oxidative potentials), a cDNA released from the electrode can quantitatively control the activation of DNA nanodevice. From this report, a new system is successfully demonstrated to precisely control DNA release on demand. By applying more advanced form of DNA‐based nanodevices into multilayer system, the electro‐responsive nanoplatform will expand the availability of DNA nanotechnology allowing its improved application in areas such as diagnosis, biosensing, bioimaging, and drug delivery. Abstract : Electroresponsive multilayer nanofilm controls spontaneous activation of a DNA nanodevice by incorporating and releasing a complementary DNA strand in a precisely controlled manner via electronic inputs. The multilayer film is produced by layer‐by‐layer assembly technique which fabricates exquisitely designed multilayer films with various materials at the nanoscale. This nanofilm as a platform can extend a field of DNA nanodevice applications.